Experimental investigation and CFD simulation of helicopter tail rotor blade - Firdaus Mahamad, 1987-, author 554695; Mohd. Shariff Ammoo 435058; Eng. Jaswar Koto 639449; Iskandar Shah Ishak, 1973- 521953; Fakulti Kejuruteraan Mekanikal 8081 (Johor Bahru, Johor : Universiti Teknologi Malaysia, 2016)
Thesis (Sarjana Kejuruteraan (Teknologi Marin))